NEBULA: WEB-BASED INTERACTIVE DASHBOARD FOR MONITORING TUBERCULOSIS CASES IN SEMARANG CITY - Rifamuthia, Titis; Dewi, Ika Novita; Isworo, Slamet; Handayani, Sri; Sholikun, Sholikun (Departemen Teknik Elektro, Universitas Diponegoro, 2025)
Tuberculosis (TB) remains a critical public health concern, particularly in developing nations like Indonesia, where it remains one of the leading causes of mortality. In Semarang City, as of July 2024, 1,624 TB cases were reported, emphasizing the need for robust monitoring systems. While various efforts have been made to reduce TB transmission, challenges such as fragmented data sources and limited access to real-time information hinder effective intervention. This study presents the development of NEBULA (New Breath for Lungs), a web-based interactive dashboard designed to visualize and monitor the spread of TB in Semarang City. Built using Tableau, the dashboard incorporates real-time data filtering and drill-down capabilities, allowing users to analyse TB cases based on parameters such as time, gender, and location. The system aims to assist local health authorities and the general public in tracking TB cases, identifying high-risk areas, and enabling more informed decision-making. By providing clear and actionable data visualization, NEBULA enhances public health surveillance and can serve as a model for managing infectious diseases in other regions. Future enhancements include incorporating predictive analytics to further improve TB management and prevention strategies.